Geodesic acoustic mode investigation in the spherical Globus-M tokamak using multi-diagnostic approach. (17th December 2015) - Bulanin, V.V.; Gusev, V.K.; Iblyaminova, A.D.; Khromov, N.A.; Kurskiev, G.S.; Minaev, V.B.; Patrov, M.I.; Petrov, A.V.; Petrov, Yu.V.; Sakharov, N.V.; Shchegolev, P.B.; Tolstyakov, S.Yu.; et al.
Abstract: The results of a multi-diagnostic approach for geodesic acoustic mode (GAM) studies in the spherical torus Globus-M are presented. The GAM oscillations of radial electric field, plasma density and magnetic field were simultaneously observed. The spatial structures of crucial plasma parameters are exhibited and discussed. The intermittent character of the GAM manifests itself as a modulation at two time-scales: equilibrium time scale and the characteristic time for limit-cycle oscillations. The mutual influence of GAM oscillations and turbulence is demonstrated by bicoherence analysis.